A new developmental mechanism for the separation of the mammalian middle ear ossicles from the jaw. Issue 1848 (8th February 2017) - Urban, Daniel J.; Anthwal, Neal; Luo, Zhe-Xi; Maier, Jennifer A.; Sadier, Alexa; Tucker, Abigail S.; Sears, Karen E.
Abstract : Multiple mammalian lineages independently evolved a definitive mammalian middle ear (DMME) through breakdown of Meckel's cartilage (MC). However, the cellular and molecular drivers of this evolutionary transition remain unknown for most mammal groups. Here, we identify such drivers in the living marsupial opossum Monodelphis domestica, whose MC transformation during development anatomically mirrors the evolutionary transformation observed in fossils. Specifically, we link increases in cellular apoptosis and TGF-BR2 signalling to MC breakdown in opossums. We demonstrate that a simple change in TGF-β signalling is sufficient to inhibit MC breakdown during opossum development, indicating that changes in TGF-β signalling might be key during mammalian evolution. Furthermore, the apoptosis that we observe during opossum MC breakdown does not seemingly occur in mouse, consistent with homoplastic DMME evolution in the marsupial and placental lineages.